Primary Left Cardiac Angiosarcoma with Mitral Valve Involvement Accompanying Coronary Artery Disease - Cagdas Baran; Serkan Durdu; Sadik Eryilmaz; Mustafa Sirlak; A. Ruchan Akar (Case Reports in Surgery)
We report here on a 43-year-old female patient presenting with non-ST elevation myocardial infarction, severe mitral regurgitation, and mild mitral stenosis secondary to encroachment of the related structures by a primary cardiac angiosarcoma. A coronary angiography revealed significant stenosis in the left main and left circumflex arteries and at exploration, the tumour was arising from posterior left atrial free wall, invading the posterior mitral leaflet, and extending into all of the pulmonary veins and pericardium. Therefore, no further intervention was performed, except for left internal mammarian artery to left anterior descending artery anastomosis and biopsy. As far as we know, this case is unique with respect to its presentation.